Sterilization of dielectric containers using a fore-vacuum pressure plasma-cathode electron source. (October 2015) - Zolotukhin, D; Burdovitsini, V; Oks, E; Tyunkov, A; Yushkov, Yu
Abstract: We describe our work on sterilization of 10 ml glass and 60 ml plastic cylindrical containers using a fore-vacuum pressure, plasma-cathode, electron beam source. Beam plasma is formed inside the vessel by injection of a low-energy electron beam at 3 - 6 keV energy and current of 50 mA, at a working gas (air) pressure of 8 Pa. The gas composition was tracked by a quadrupole gas analyzer type RGA-100. As a test biological object for sterilization we used E. coli ATCC 25922 bacteria, the inner surface of each vessel was inoculated with a bacterial suspension. We find a smooth dependence of the degree of sterilization on the total energy density injected into the vessel. The efficacy of sterilization of container inner surfaces using a fore-vacuum pressure, plasma-cathode e-beam source of relatively low energy (a few keV) electrons is thus demonstrated.